Analysis of Importance of Emotional Quotient in Education - VERMA, RAJIV; JAIN, VIPIN; SETHI, PUNEET (The journal of contemporary issues in business and government, 2021)
Emotional intelligence has been focused in recent times as the competition is going to increase day by day. The handle of the emotional become more relevant in the competitive atmosphere. The youngster has to face the competition in their studies and sport, the adult has to handle their carries and sometimes their love life also. The employed person has to face a lot of stress at their workplace; even today’s fast-moving world has no guarantee of any misfortune in an individual’s life. Therefore, one needs to be emotionally enough strong to handle or control their emotions to come out from any unexpected circumstances. The emotional quotient has become a more sensitive issue to discuss apart from the intelligence quotient. The present paper has been written to address the level of the emotional intelligence of school-going students.